Market fragility and the paradox of the recent stock-bond dissonance - Christos Koulovatianos; Jian Li; Fabienne Weber (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
After the Lehman-Brothers collapse, the stock index has exceeded its pre-Lehman-Brothers peak by 36% in real terms. Seemingly, markets have been demanding more stocks instead of bonds. Yet, instead of observing higher bond rates, paradoxically, bond rates have been persistently negative after the Lehman-Brothers collapse. To explain this paradox, we suggest that, in the post-Lehman-Brothers period, investors changed their perceptions on disasters, thinking that disasters occur once every 30 years on average, instead of disasters occurring once every 60 years. In our asset-pricing calibration exercise, this rise in perceived market fragility alone can explain the drop in both bond rates and price-dividend ratios observed after the Lehman-Brothers collapse, which indicates that markets mostly demanded bonds instead of stocks.
urn:nbn:de:hebis:30:3-437394
Keywords: G12; G01; E44; E43; 330; asset pricing; disaster risk; price-dividend ratio; bond returns